DESAFIOS E CAMINHOS PARA A CONSTRUÇÃO DE AGROECOSSISTEMAS RESILIENTES - Guatimosim, Eduardo; Goncalves Rosa Pacheco, Clécia Simone; Oliveira Jr., Clovis José Fernandes de; Vidal, Mariane Carvalho (Revista Brasileira de Agroecologia, 2023)
DESAFIOS E CAMINHOS PARA A CONSTRUÇÃO DE AGROECOSSISTEMAS RESILIENTES Configurações